Survey of body part symptoms among workers in a car tyre service centre - Abdol Rahman, Mohd Nasrull; Abdul Aziz, Faieza; Mohd Yusuff, Rosnah (Human Ergology Society, 2010)
The purpose of this study was to investigate the prevalence of body part symptoms and sources of injury/discomfort among workers in a car tyre service centre. Questionnaire survey and interview session were used to identify the level of body discomfort areas and sources of injury or discomfort. From questionnaire survey findings, 12 of respondents have body discomfort in the neck (66.7%), shoulder (83.3%), elbow/forearm (75%), hand/wrist (91.7%), knee (58.3%), lower leg (75%), ankle/foot (33%) and lower back (30%). The main sources of injury/discomfort in the workplace were poor body posture (75%), bending the back (75%), highly repetitive motions (75%), lifting heavy objects (83.3%), the long-term standing (66.7%), long-term squatting (58.3%), bending the neck (66.7%) and high hand force (58.3%). About 50% reported that poor workplace design also contributed to injury while 41.7% mentioned the use of hand tools. To address modifying the ergonomic hazards, engineering controls and administrative controls can be used. The study will be useful to ergonomists, researchers, consultants, workshop managers, maintenance workers and others concerned with identifying body part symptoms and sources of injury/discomfort at the workplace.